ANALGETIC ACTIVITY TEST OF ETHANOL EXTRACT SUNGKAI LEAF (Peronema canescens Jack) IN WHITE MALE MOUSE (Mus musculus) INDUCED WITH ACETIC ACID - Lia Wahyuni; Dona Muin; Defirson Defirson; Andy Brata (Jurnal Farmasi Sains dan Praktis, 2023)
Traditional medicine, which is generally considered safer than modern medicine, makes people choose alternative treatments using medicinal plants, one of which is to treat pain. One of the medicinal plants used to treat pain is a plant that contains flavonoids, one of which is the Sungkai plant (Penorema canescens Jack). The research design used was The Static Group Comparison, where the test animals used were divided into 5 groups, each group consisting of 5 mice. Group 1 was given 1 percent of CMC. Group II was given ethanol extract of Sungkai leaves at a dose of 300 mg/Kg BW. Group III was given EEDS at a dose of 600 mg/kg BW. Group IV was given EEDS at a dose of 900 mg/Kg BW. Group V was given paracetamol suspension. The results showed that there was an analgesic activity in the EEDS group, dose I was 50 percentage, dose II was 55,798 percentage, and dose III was 69,564 percentage. The study concluded that statisti-cally there was no significant difference in analgesic activity in white male mice between the EEDS doses I, II, and III groups and the paracetamol group.